2017
DOI: 10.1371/journal.pone.0169845
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio for Predicting Loss of Response to Infliximab in Ulcerative Colitis

Abstract: ObjectivesNeutrophil-to-lymphocyte ratio (NLR) has been used to determine the outcome in malignancies and coronary heart disease. Some reports considered the value of NLR as a predictor of response to infliximab in patients with Crohn’s disease or rheumatoid arthritis; however, no similar studies have been reported for ulcerative colitis (UC). This study aimed to evaluate the clinical significance of the baseline NLR in patients with UC treated by infliximab.Materials and MethodsPatients with moderate-to-sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 36 publications
0
58
1
1
Order By: Relevance
“…Subsequently, the predictive value of NLR for clinical response to infliximab in UC patients was also examined in one study involving 59 patients with moderate‐to‐severe active UC treated with infliximab, and 37 patients experienced clinical response after induction therapy. During the observational period, 14 of 37 patients on maintenance therapy lost the response, and the NLR baseline levels of patients who lost to response were significantly higher than those in patients with sustained response . Taken together, these two studies indicated that the pre‐treatment levels of NLR could serve as predictor of sustained response to a 52‐week course of infliximab therapy among patients with CD and UC, and taking NLR into account in patients with CD and UC may lead to more appropriate clinical management of those patients treated with infliximab.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Subsequently, the predictive value of NLR for clinical response to infliximab in UC patients was also examined in one study involving 59 patients with moderate‐to‐severe active UC treated with infliximab, and 37 patients experienced clinical response after induction therapy. During the observational period, 14 of 37 patients on maintenance therapy lost the response, and the NLR baseline levels of patients who lost to response were significantly higher than those in patients with sustained response . Taken together, these two studies indicated that the pre‐treatment levels of NLR could serve as predictor of sustained response to a 52‐week course of infliximab therapy among patients with CD and UC, and taking NLR into account in patients with CD and UC may lead to more appropriate clinical management of those patients treated with infliximab.…”
Section: Discussionmentioning
confidence: 86%
“…Apart from the value of assessing disease activity, a few studies were performed to determine the clinical value of NLR and PLR in treatment response in the field of rheumatology . In a study involving 358 RA patients treated with bDMARDs (infliximab, etanercept, adalimumab, TCZ, and abatacept), NLR decreased significantly after treatment with each bDMARDs except for abatacept, and △NLR was positively correlated with △DAS28‐ESR, indicating that △NLR might be applied to reflect the efficacy of bDMARDs .…”
Section: Discussionmentioning
confidence: 99%
“…The value of albumin, haemoglobin and CRP for predicting anti‐TNF response has been reported in several studies (Table S7). Evidence from one study suggests that baseline neutrophil‐to‐lymphocyte ratio predicts secondary loss of response to IFX treatment in UC patients (HR 3.86 [1.20‐12.4], P = 0.023; AUC 0.798) …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we used not only NLR but also MER and PLR as indicative parameters of systemic inflammation in the present study. Inflammation parameters such as NLR, MER, and PLR have an important role in inflammatory, oncologic, and cardiovascular diseases (Imtiaz et al ., ; Nishida et al ., ). Yoon et al .…”
Section: Discussionmentioning
confidence: 97%
“…Our study revealed a cutoff value of 1.8 (AUC 0.712, p < 0.001; sensitivity 61.1%; specificity 75.0%) discrimination of the phases of PD for the NLR. Various cutoff values have been found in different studies for NLR ranged between 1 and 5 (Nishida et al ., ; Yucel et al ., ; Ventimiglia et al ., ). Forget et al .…”
Section: Discussionmentioning
confidence: 97%